Resilient virtual synchronous generator approach using DC-link capacitor energy for frequency support of interconnected renewable power systems. (15th August 2023) - Bakeer, Mahmoud; Magdy, Gaber; Bakeer, Abualkasim; Aly, Mohamed M.
Abstract: Modern interconnected power systems with many renewable energy sources (RESs) are more susceptible to disturbances than conventional power systems because they lack the inertia constant. Therefore, this study presents an advanced frequency control strategy for interconnected power systems considering high RESs penetration relying on the virtual inertia control (VIC) strategy-based high voltage direct current (HVDC) link, thus improving the dynamic frequency performance of future power systems. The HVDC link has been used as a DC capacitor which stores the electrostatic energy. This stored energy can supply the earliest active power support in automatic generation control system operation. Moreover, this paper develops the conventional VIC strategy based on the HVDC link by considering the dynamic behavior of a virtual rotor that mimics the inertia and damping properties of actual synchronous machines, thus stabilizing future renewable power systems. Also, this paper proposes a novel frequency control scheme based on the inertia emulation-based HVDC link and a virtual synchronous generator, which mimics the virtual rotor and virtual frequency control loops, to improve further the frequency regulation of low-inertia modern interconnected power systems. The parameters of the virtual synchronous generator scheme are optimally adjusted utilizing particle swarm optimization. The utility and superiority of the proposed VIC strategies based on the HVDC link are confirmed by contrasting them with the conventional VIC strategy relying on the HVDC link in the studied interconnected power system against various load/renewables interruptions, uncertainties, and physical restrictions. MATLAB/Simulink® software was used to simulate the results of the investigated system. Highlights: Proposing a new frequency control strategy based on the VIC strategy using the energy storage in the DC-link capacitor. Studying frequency stability issue of AC/DC interconnected modern power systems. Developing a VIC strategy based on the HVDC link by considering the dynamic behavior of a virtual rotor. Proposing a novel frequency control scheme based the HVDC link's energy along with a virtual synchronous generator. The uncertainties of RESs/loads and system nonlinearities are considered during the design of the proposed controllers.